Composition of Macrobenthos in the Wouri River Estuary Mangrove, Douala, Cameroon - Ngo-Massou, Vanessa Maxemilie; Koum, Guillaume Léopold Essome; Dina, Emmanuel Ngollo; Din, Ndongo (Taylor and Francis, 2013)
The macrobenthos of mangroves is dominated by crabs and molluscs, which have a significant ecological role in terms of the structure and function of mangroves. The aim of this study was to determine the abundance and biological diversity of these groups in the Wouri River estuary mangrove in Douala, Cameroon. Three methods of crabs capture (excavation, sight harvest and visual count) were used in 10 × 10 m2 plots for the crabs and quadrats of 1 × 1 m2 were employed for mollusc counts. In all, 24 species, evenly distributed between the two groups, were collected. Five families of crabs and six families of molluscs were identified. Sesarmidae (eight species) and Pachymelaniidae (four species) were best represented in terms of species richness, whereas Sesarmidae (94.6%) and Potamididae (45.6%) were the most abundant taxa. The inventory of macrobenthos of mangroves in Cameroon currently consists of 60 species, including nine (three crabs and six of molluscs) reported from this study.